Building Capacity to Trade What Are the Priorities? - Solignac Lecomte, Henri-Bernard (OECD Development Centre Working Papers, 2003)
The Doha Declaration stresses the "important role" of "well targeted, sustainably financed technical assistance and capacity-building programmes". It dedicates a whole section to them, and reiterates the commitment of its membership to help the weakest among them participate effectively in the multilateral trade system. What does this mean in practice? What exactly is the purpose of "trade capacity building" (TCB)? Who should provide this assistance and how? Is it all gain for developing countries, or does it entail risks? As more and more funds are earmarked for TCB, often for the benefit of countries with very low absorption capacity, recipients and donors need clear answers to these questions. Based on a recent review of trade capacity building projects administered in African and Caribbean countries, and on recent analytical work in Eastern Africa, this paper attempts to provide some elements of response2 ...